2020
DOI: 10.3889/oamjms.2020.4946
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Pregnancy Prevention Behavior in Indonesia: Internal and External Factors Influencing

Abstract: BACKGROUND: The reasons behind teenage pregnancy and marriage in Indonesia are the lack of life skills and low self-efficacy. Teenagers with a lack of life skills are more likely to be influenced by their peers, in this case, to have sex before marriage. Teenage pregnancy often leads to a high rate of maternal and infant mortality and high-risk infants. AIM: This study aimed to identify internal and external factors influencing adolescent pregnancy prevention behavior. METHODS: This quantitative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that adolescents have a higher rate of preterm labour compared to women of reproductive age (Exarchos et al, 2022). This increased risk of preterm birth among adolescents has been supported by several studies (Deswinda et al, 2020). Other risk factors such as low educational attainment, previous abortions, and previous preterm births have also been found to contribute to a higher incidence of preterm birth in teenage pregnancy (Nurdiawan et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Studies have shown that adolescents have a higher rate of preterm labour compared to women of reproductive age (Exarchos et al, 2022). This increased risk of preterm birth among adolescents has been supported by several studies (Deswinda et al, 2020). Other risk factors such as low educational attainment, previous abortions, and previous preterm births have also been found to contribute to a higher incidence of preterm birth in teenage pregnancy (Nurdiawan et al, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…The prevalence of teenage pregnancy in Indonesia is quite high compared to other developing countries, with prevalence rates ranging from 0.6% to 15.4% (Deswinda et al, 2020). In a study conducted in Indonesia, the prevalence of teenage pregnancy was found to be 10.05% (Nurdiawan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risky sexual behavior is known as behavior carried out by adolescents consciously. Same sex or different sex of sexual desire was done without any consideration of any norms or applicable rules [4], [5]. Unfortunately, westernization much more influences Indonesian adolescents' reproductive health in the middle of cultural and social tradition, specifically its Islamic culture among society [6].…”
Section: Introductionmentioning
confidence: 99%